The Influence of Surface Polish and Beverages on the Roughness of Nanohybrid and Microhybri Resin Composites - Sadeghi M; Deljoo Z; Bagheri R (Shiraz University of Medical Sciences, 2016)
Statement of the Problem: Surface roughness is a key factor in the aesthetics of restorative dentistry as it can determine the clinical quality and success of restorative materials. The chemical process of dissolution in the presence of mechanical forces can accelerate the surface roughness of tooth-coloured restorative materials. Objectives: To determine the degree of surface roughness of a microhybrid and a nanohybrid resin composite after polishing and immersion in various solutions. Materials and Methods: Two resin composites were used : a microhybrid (Gradia direct, GC), and a nanohybrid (Ice, SDI). A total of 54 disc-shaped specimens were prepared for each composite and immersed in distilled water incubated at 37 °C for 24 hours. After 24 h, the baseline measurement for surface roughness (Ra) was performed and the specimens were divided into 3 groups of 18 and tested with unpolished or after polishing with Sof-Lex disc and Enhance point systems. Specimens in each group were subdivided into 3 subgroups (n = 6) and immersed in 3 solutions (distilled water, coffee, and cola) for 7 days incubated at 37 °C. After 7 days, the specimens were rinsed with tap water for 10 seconds, dried with paper towel and Ra was measured again. Two randomly selected specimens of each group were sputter coated with gold and examined using a Field-Emission Scanning Electron Microscope (SEM). Results: Gradia direct showed a greater Ra than ice in all solutions for all polishing systems (p < 0.001). Specimens polished with Enhance point revealed a significantly greater roughness than Sof-Lex discs and both showed greater Ra than unpolished specimens. Specimens immersed in coffee exhibited significantly greater surface roughness than that of distilled water (p < 0.05) and cola (p < 0.001). Conclusions: Nano-hybrid composite showed a significantly smoother surface than microhybrid. Coffee exhibited the highest Ra compared to distilled water and cola. Enhance point revealed significantly greater Ra than Sof-Lex discs and unpolished group.